Implementation and sustainability of safe consumption sites: a qualitative systematic review and thematic synthesis - Grace H. Yoon; Timothy W. Levengood; Melissa J. Davoust; Shannon N. Ogden; Alex H. Kral; Sean R. Cahill; Angela R. Bazzi (Harm Reduction Journal, 2022)
Abstract Background Safe consumption sites (SCSs) serve diverse populations of people who use drugs (PWUD) and public health objectives. SCS implementation began in the 1980s, and today, there are at least 200 known SCSs operating in over twelve countries. While a growing literature supports their effectiveness as a harm reduction strategy, there is limited information on contextual factors that may support or hinder SCS implementation and sustainability. We aimed to fill this gap in knowledge by reviewing existing qualitative studies on SCSs. Methods We conducted a systematic review and thematic synthesis of qualitative studies. We identified all peer-reviewed, English-language qualitative studies on SCSs containing original data in PubMed, Web of Science, Google Scholar, and Science Direct as of September 23, 2019. Two authors independently screened, abstracted, and coded content relating to SCS implementation and sustainment aligned with the Exploration, Preparation, Implementation, Sustainment (EPIS) implementation science framework. Results After removing duplicates, we identified 765 unique records, of which ten qualitative studies met inclusion criteria for our synthesis. Across these ten studies, 236 total interviews were conducted. Overall, studies described how SCSs can (1) keep drug use out of public view while fostering a sense of inclusion for participants, (2) support sustainment by enhancing external communities’ acceptability of SCSs, and (3) encourage PWUD utilization. Most studies also described how involving PWUD and peer workers (i.e., those with lived experience) in SCS operation supported implementation and sustainability. Discussion Our thematic synthesis of qualitative literature identified engagement of PWUD and additional factors that appear to support SCS planning and operations and are critical to implementation success. However, the existing qualitative literature largely lacked perspectives of SCS staff and other community members who might be able to provide additional insight into factors influencing the implementation and sustainability of this promising public health intervention.